2016
DOI: 10.1158/0008-5472.can-15-1542
|View full text |Cite
|
Sign up to set email alerts
|

Activated Thyroid Hormone Promotes Differentiation and Chemotherapeutic Sensitization of Colorectal Cancer Stem Cells by Regulating Wnt and BMP4 Signaling

Abstract: Thyroid hormone is a pleiotropic factor that controls many cellular processes in multiple cell types such as cancer stem cells (CSC). Thyroid hormone concentrations in the blood are stable, but the action of the deiodinases (D2-D3) provides cell-specific regulation of thyroid hormone activity. Deregulation of deiodinase function and thyroid hormone status has been implicated in tumorigenesis. Therefore, we investigated the role of thyroid hormone metabolism and signaling in colorectal CSCs (CR-CSC), where deio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 25 publications
0
44
1
Order By: Relevance
“…Even more intriguingly, a recent work (Catalano et al 2016) showed that T 3 treatment induces differentiation of colorectal cancer stem cells (CR-CSCs), by increasing the levels of the bone morphogenetic protein (BMP4, a known promoter of differentiation in normal colonic epithelium) and of its downstream targets. The same work also showed that increasing intracellular levels of T 3 results in reduced 23:8 clonogenic and tumourigenic potential and establishes a higher sensitivity of CR-CSCs to chemotherapy, supporting the hypothesis that T 3 may inhibit tumour development by activating a differentiation program.…”
Section: T 3 /Trs Axis and Cell Differentiationmentioning
confidence: 99%
“…Even more intriguingly, a recent work (Catalano et al 2016) showed that T 3 treatment induces differentiation of colorectal cancer stem cells (CR-CSCs), by increasing the levels of the bone morphogenetic protein (BMP4, a known promoter of differentiation in normal colonic epithelium) and of its downstream targets. The same work also showed that increasing intracellular levels of T 3 results in reduced 23:8 clonogenic and tumourigenic potential and establishes a higher sensitivity of CR-CSCs to chemotherapy, supporting the hypothesis that T 3 may inhibit tumour development by activating a differentiation program.…”
Section: T 3 /Trs Axis and Cell Differentiationmentioning
confidence: 99%
“…There are several other signaling pathways which have important contribution to CSC maintenance (schematic representation in Figure 1). The role of Notch [27, 28], TGF-beta [29, 30], and Wnt [31, 32] in CSC maintenance has been extensively reported. These molecules are also in clinical trials to aid in radiation therapy.…”
Section: Cscs and Molecular Mechanisms Regulating Radiation Responsementioning
confidence: 99%
“…5) [48]. Recently, this hypothesis has been again supported by Catalano and coworkers [28], who have found that increased intracellular TH concentration through D3 depletion induces cell differentiation and sharply mitigates tumor formation.…”
Section: Reviewmentioning
confidence: 87%